The Impact of Busy Commissioners, Profitability, and Firm Size on Firm Value of Conventional Commercial Banks Listed on the Indonesia Stock Exchange - Padillah, Muhammad Ega; Sutrisno, Bambang (Dinasti Publisher, 2026)
This study examines the impact of busy commissioners, profitability, and firm size on firm value in conventional commercial banks listed on the Indonesia Stock Exchange from 2020 to 2024. Firm value is a crucial indicator that reflects investors’ assessments of a company’s performance, financial strength, and future growth prospects, particularly in the banking sector, which plays a vital role in maintaining economic stability and supporting national development. This research employs a quantitative approach, utilizing secondary data collected from audited annual reports and financial statements of each conventional commercial bank's website. The research population comprises all conventional commercial banks listed on the Indonesia Stock Exchange. The sample was selected using a purposive sampling method, resulting in ten banks with the largest total assets during the observation period. This study employs panel regression with a fixed effects model. The findings reveal that busy commissioners have a statistically insignificant negative impact on firm value. Profitability positively and insignificantly impacts firm value. Firm size has a negative and insignificant effect on firm value. The findings suggest that banks should consider other factors that potentially affect bank value.